LEADING WITH AMANAH: THE MEDIATING ROLE OF ISLAMIC WORK ETHICS IN THE RELATIONSHIP BETWEEN SPRITUAL LEADERSHIP AND KNOWLEDGE SHARING - Reijeng Tabara; Andi Hasrun; Nurjannah (Academic Bright Collaboration, 2026)
Drawing on Social Learning Theory and Islamic Ethics, this study develops and tests a model examining the mediating role of Islamic Work Ethics in the relationship between spiritual leadership and knowledge sharing. A quantitative cross-sectional survey was conducted among 248 employees from two Islamic nongovernmental organizations (NGOs) operating in Southwest Papua, Indonesia. The proposed hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The findings reveal that spiritual leadership exerts a positive and significant influence on both knowledge sharing and Islamic Work Ethics. Islamic Work Ethics also positively and significantly affects knowledge sharing. Furthermore, the indirect effect of spiritual leadership on knowledge sharing through Islamic Work Ethics is significant, indicating a partial mediation role. The proposed model explains 81.5% of the variance in knowledge-sharing behavior. The findings suggest that leaders of Islamic NGOs should invest strategically in spiritually grounded leadership development and initiatives aimed at strengthening Islamic Work Ethics to foster a more collaborative knowledge-sharing culture. However, the cross-sectional design and the focus on a single regional context limit the ability to draw causal conclusions and constrain the generalizability of the findings to other organizational settings. This study contributes to the Islamic management and organizational behavior literature by empirically examining Islamic Work Ethics as a mediating mechanism linking spiritual leadership and knowledge sharing. It also extends the existing literature by providing evidence from Islamic NGOs operating in a frontier Muslim-minority context in Eastern Indonesia, a setting that remains largely underexplored in prior research.